Nuevas lecciones de arquitectura moderna - Capitel, Antón, 1947- (Textos de arquitectura y diseño., 2011)
Anthology comprising a selection of articles and short critical essays on modern and contemporary architecture, architects and urban spaces written from 2002 to 2008 by architect, historian and critic Antón Capitel, academic of project of the Escuela de Arquitectura in Madrid. All the texts are accompanied by black and white photographs, sketches and plans.